2022
DOI: 10.1039/d2gc00799a
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical aerobic oxidation of sulfides to sulfoxides: the crucial role of wavelength irradiation

Abstract: The sulfoxide moiety is recognized as one of the most important groups in organic and medicinal chemistry. Many efforts worldwide focus on developing novel and sustainable protocols, accessing sulfoxide-containing molecules....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 105 publications
2
28
0
Order By: Relevance
“…Again, this is a slightly decreased reaction time compared with our previous studies (2 h vs. 3 h). 26 Quantitative formation of the desired sulfoxide was also obtained when GVL or water was used as the solvent (Table 2, entries 3 and 5); however, lower yields were obtained upon isolation (60% and 68%, respectively). Furthermore, GVL and water might pose difficulties when the catalyst-free protocol is used in the pharmaceutical industry.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Again, this is a slightly decreased reaction time compared with our previous studies (2 h vs. 3 h). 26 Quantitative formation of the desired sulfoxide was also obtained when GVL or water was used as the solvent (Table 2, entries 3 and 5); however, lower yields were obtained upon isolation (60% and 68%, respectively). Furthermore, GVL and water might pose difficulties when the catalyst-free protocol is used in the pharmaceutical industry.…”
Section: Resultsmentioning
confidence: 93%
“…Indeed, 2-Me-THF was the solvent of choice, reducing the reaction time at the same time, in comparison with our previous results. 26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Also, anthraquinone is known to participate in HAT processes, 23 while it can also generate singlet oxygen. 32 Fluorescent quenching studies were then performed (Figure 1). After irradiation of anthraquinone (2b) (1 mM in MeCN) at 358 nm, its fluorescence was measured at 404 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Since our control experiments showed that singlet oxygen could also play a role in the process, a secondary pathway is also proposed (Scheme 8, B). The triplet state anthraquinone is capable of generating singlet oxygen, 32 leading to the mechanism proposed in Scheme 8, B. Singlet state oxygen is capable to perform a direct insertion in the activated benzylic C-H bond of PS, 29 leading to IX. Also, the decomposition of the high energy peroxy intermediates can lead to reactive oxygen species (ROS), including hydroxyl radical and superoxide anion, which are highly oxidative and potent hydrogen atom Then a similar β-scission can occur leading to VI and VII, following then the same pathway as in Scheme 8, A.…”
Section: Resultsmentioning
confidence: 99%